PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sub Sektor Property dan Real Estate yang Terdaftar di BEI 2018-2020) - Laras Pangestu; Triyono Triyono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The value of a company is determined by financial decisions such as investment, financing, and dividend policy. Shareholders have a strategy to increase their wealth by increasing the value of the company. This study aims to determine the effect of liquidity, leverage, profitability, activity, and firm size on firm value. The measure of firm value used in this study is PBV. The application used to process the data in this research is SPSS 21. The research method used is a quantitative approach. The sample used in this study found 153 which is data for 3 years, namely 2018-2020. The results of this study indicate that there are 2 independent variables that have a positive effect on firm value, namely profitability and activity. While the other 3 independent variables, namely liquidity, leverage, and firm size have no effect on firm value.